Crip theory: cultural signs of queerness and disability - MacRuer, Robert (New York University Press, 2006)
A bold and contemporary discourse of the intersection of disability studies and queer studies Crip Theory attends to the contemporary cultures of disability and queerness that are coming out all over. Both disability studies and queer theory are centrally concerned with how bodies, pleasures, and identities are represented as “normal” or as abject, but Crip Theory is the first book to analyze thoroughly the ways in which these interdisciplinary fields inform each other. Drawing on feminist theory, African American and Latino/a cultural theories, composition studies, film and television studies, and theories of globalization and counter-globalization, Robert McRuer articulates the central concerns of crip theory and considers how such a critical perspective might impact cultural and historical inquiry in the humanities. Crip Theory puts forward readings of the Sharon Kowalski story, the performance art of Bob Flanagan, and the journals of Gary Fisher, as well as critiques of the domesticated queerness and disability marketed by the Millennium March, or Bravo TV’s Queer Eye for the Straight Guy. McRuer examines how dominant and marginal bodily and sexual identities are composed, and considers the vibrant ways that disability and queerness unsettle and re-write those identities in order to insist that another world is possible.
Section: 283 pages : illustrations
Keywords: EDI; LGBTQIA2+; approches et analyses; art; cours; crip; discipline; militance; premier cycle; queer; santé; soc2014; thématiques; études critique du handicap; études littéraires

Queering the Crip or Cripping the Queer?: Intersections of Queer and Crip Identities in Solo Autobiographical Performance - Sandahl, Carrie (GLQ: A Journal of Lesbian and Gay Studies, 2003)
As the interdisciplinary field of disability studies develops its own theoretical paradigms, it necessarily borrows from various sources. Such borrowing means that disability scholars have not had to reinvent the wheel but have been able to build on the conceptual foundations of identity-based theories that have grown out of other interdisciplinary fields, such as gender studies and critical race studies. But disability studies offers as much to its predecessors as it borrows from them. This essay explores the productive reciprocity between queer theory and disability studies, queer identity and crip identity, queer activism and crip activism.
Keywords: EDI; LGBTQIA2+; approches et analyses; arts; capacitisme; care; corps; cours; crip; discipline; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lit4700; militance; premier cycle; queer; ressource en ligne; santé; systèmes d'oppressions; thématiques; théâtre; études littéraires

Journal de la création - Huston, Nancy (Actes sud, 2001)
Pendant des millénaires, tout paraissait simple : aux hommes la création, aux femmes la procréation ; aux hommes l'esprit et aux femmes le corps. L'émancipation féminine a bousculé cette distribution des rôles et mis à mal des métaphores séculaires : la muse féminine, l'œuvre d'art comme amante ou comme " enfant " de l'artiste. Mais trouver un nouveau modus vivendi n'est pas facile pour autant. Mettant à profit une certaine et curieuse forme de clairvoyance liée, dans son esprit, aux métamorphoses de son corps de femme enceinte, Nancy Huston s'est penchée sur les histoires souvent douloureuses de Sand et Musset, Virginia et Leonard Woolf, Scott et Zelda Fitzgerald, Sartre et Beauvoir. Le récit de ses recherches sur les couples d'écrivains et le journal de sa propre grossesse se croisent, se répondent et se complètent pour évoquer les mystères de l'amour, de l'inspiration, du couple et de la création.
Donné en lecture : 11-56
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; corps; cours; création; discipline; europe; fem1000; littérature; premier cycle; procréation; périodes historiques; régions géographiques; santé; santé reproductive; thématiques; études littéraires